Statistical analysis of the correlation between the equatorial electrojet and the occurrence of the equatorial ionisation anomaly over the East African sector - Mungufeni, Patrick; Habarulema, John Bosco; Migoya-Orué, Yenca; Jurua, Edward (In Annales Geophysicae, 2018)
This study presents statistical quantification of the correlation between the equatorial electrojet (EEJ) and the occurrence of the equatorial ionisation anomaly (EIA) over the East African sector. The data used were for quiet geomagnetic conditions (Kp _3) during the period 2011–2013. The horizontal components, H, of geomagnetic fields measured by magnetometers located at Addis Ababa, Ethiopia (dip lat. _ 1_ N), and Adigrat, Ethiopia (dip lat. _ 6_ N), were used to determine the EEJ using differential techniques. The total electron content (TEC) derived from Global Navigation Satellite System (GNSS) signals using 19 receivers located along the 30–40_ longitude sector was used to determine the EIA strengths over the region. This was done by determining the ratio of TEC over the crest to that over the trough, denoted as the CT: TEC ratio. This technique necessitated characterization of the morphology of the EIA over the region. We found that the trough lies slightly south of the magnetic equator (0–4_ S). This slight southward shift of the EIA trough might be due to the fact that over the East African region, the general centre of the EEJ is also shifted slightly south of the magnetic equator. For the first time over the East African sector, we determined a threshold daytime EEJ strength of _40 nT that is mostly associated with prominent EIA occurrence during a high solar activity period. The study also revealed that there is a positive correlation between daytime EEJ and EIA strengths, with a strong positive correlation occurring during the period 13:00–15:00 LT.
Keywords: Ionosphere (equatorial ionosphere